Odpowiedź :
a) -3,6·a=[tex]1\frac{1}{5}[/tex]
-3,6a=[tex]\frac{6}{5}[/tex] |:(-3,6)
x=[tex]-\frac{1}{3}[/tex]
b:9=[tex]1\frac{2}{3}[/tex]
[tex]\frac{b}{9}[/tex]=[tex]\frac{5}{3}[/tex] |·9
b=15
b) 1,5·x=[tex]-2\frac{3}{4}[/tex]
1,5x=[tex]-2\frac{3}{4}[/tex] |:1,5
x=[tex]\frac{11}{6}[/tex]
x=[tex]1\frac{5}{6}[/tex]
y:([tex]-1\frac{5}{6}[/tex]) =-0,6
y:([tex]\frac{11}{6}[/tex])=-0,6
-y·[tex]\frac{6}{11}[/tex]=-0,6
-[tex]\frac{6}{11}[/tex]y=-0,6 |·([tex]-\frac{11}{6}[/tex])
y=[tex]-\frac{11}{6}[/tex]·(-0,6)
y=[tex]-\frac{11}{6}[/tex]·([tex]-\frac{3}{5}[/tex])
y=[tex]\frac{33}{30}[/tex]
y=[tex]\frac{11}{10}[/tex]
y=[tex]1\frac{1}{10}[/tex]
c) z:2,5=[tex]-\frac{1}{5^2}[/tex]
z:[tex]\frac{5}{2}[/tex]=[tex]-\frac{1}{25}[/tex]
z·[tex]\frac{2}{5}[/tex]=[tex]-\frac{1}{25}[/tex]
[tex]\frac{2}{5}[/tex]z=[tex]-\frac{1}{25}[/tex] |·[tex]\frac{5}{2}[/tex]
z=[tex]-\frac{1}{10}[/tex]
[tex]-2\frac{2}{3}[/tex]·w=[tex](-\frac{2}{3})^2[/tex]
[tex]-\frac{8}{3}[/tex]w=([tex]-\frac{4}{9}[/tex]) |·([tex]-\frac{3}{8}[/tex])
w=[tex]-\frac{1}{6}[/tex]